Study and Investigation of the Charge Transfer Rate Production in N3-Senstized Dye Contact with ZnS Semiconductor System - Zainab Amjad Hamid; Mohsin A. Hassooni (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2025)
In this work, the rate of charge transfer (CT) reaction at the N3-ZnS interface was calculated using a quantitative computational model to evaluate the efficiency of N3-ZnS heterojunction dye-sensitized solar cell devices using different types of solvents. This work discussed the influence of the effective driving energy force on the charge transport rate and performance of N3-ZnS devices with various solvents based on a donor-acceptor model. A solar cell model was used to study the optical efficiency when changing some of its parameters, such as the type of material and the thickness of the film, as they are important factors influencing the quality of the solar cell. It was found that the transition energy varies with different solvent types depending on the dielectric constant, refractive index of the solvent, and the semiconductor, the electron transfer rate increased when the effective driving force value decreased to ∆0 =0.22 (eV) at the same temperature and charge carrier concentration, where the maximum value of the electron transfer rate for chloroform solvent was (1.0622E-06).